Minimasi Waste dengan Pendekatan Value Stream Mapping - Fandi Ahmad; Dimas Aditya (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
The problem that occurs in the packaging bottle production process is the amount of waste in it. Therefore, this study aims to make improvements in reducing waste of production time and provide recommendations for managing the production process so that in the future can be used as a reference in the production process optimization. The method used in this study is descriptive analysis conducted by examining the work and activities of an object. The results of the study show that in the production process, there was still a form of waste which, when viewed from the seven waste concept in the lean manufacturing system, there are some of the most dominant wastes such as inventory, waiting, process, overproduction, and defect. After improvement of the current mapping, the waste that occurs such as inventory, process, overproduction, waiting, and defects that occur in the production line reduced from the total lead time of 2.1 days with seven operators to 0.9 days with ten operators. Furthermore, the cycle time value of the current value stream mapping was 120.9 seconds, while the cycle time value of the proposed value stream mapping was 72 seconds. This shows an increase in productivity.